Juvenal Sanso setting the stage - Fundacion Sanso (Mandaluyong City, Philippines Southeast Asian Heritage Publication, Inc., 2016)
Of the many praises sang of the Serge Prokofieff opera "Le Joueur" (The Gambler) premiered in Toulouse last March, special mention was made of the set and costume designs of the production. With good reason. Nothing less that artistic ingenuity could cope with the fast-stepping six-act opera and its quick changes in sets, costumes, and mood. The challenge was offered to Juvenal Sanso (who we Filipinos claim as our own by virtue of his having been raised here), an honor offered only to such as Chagall, Dali, Picasso and their ilk. Sanso is the first RP artist to join the list. So, for the first time in his career, Sanso set his brush a-work on an easel larger than usual --- the theatre. With glowing results. (Woman and Home Magazine, 1 May 1966)
FA-3637g - donated by Carmela Cruz
Keywords: Juvenal, Sanso; Artists -- Philippines